Design and Evaluation of Ocular Inserts For Controlled Drug Delivery of Acyclovir - Pandey, Prasoon (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTAcyclovir is an antiviral agent used in treatment of Herpes-keratitis. In present research, an attempt has been made to formulate ocular inserts of acyclovir using various polymers such as hydroxypropylmethylcellulose, polyvinylalcohol and eudragit in different concentrations by solvent casting method using dibutylphthalate as plasticizer with aim of achieving controlled release, reduction in frequency of administration and greater therapeutic efficacy. Prepared ocuserts were evaluated for Uniformity of thickness, Uniformity of weight, Surface pH, folding endurance and drug content etc. Ocuserts are also subjected to in vitro diffusion studies. Formulation ACY-11 and ACY-17 showed zero order release was sterilized by gamma irradiation and subjected to in vivo studies, ocular toxicity test and stability studies.